Endogenous and exogenous factors influencing anti-Müllerian hormone levels in women of reproductive age - Jankowska, Olga; Kraśnik, Wojciech; Kurzeja, Jacek; Piotrowicz, Katarzyna; Piotrowicz, Hubert; Bajkacz, Agnieszka; Rogala, Anna; Osmólska, Joanna (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Anti-Müllerian hormone (AMH) is a key marker of ovarian reserve (OR), which declines with advancing reproductive age. Certain pathological conditions can reduce OR or lower AMH levels independently of age, potentially impair ing fertility. This study aims to review the scientific literature on factors influencing AMH levels and the causes of diminished OR, including lifestyle, diet, supplementation, pathogenic factors, environmental influences, and genetic predispositions. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. This review was conducted using electronic databases, including PubMed and Google Scholar. A comprehensive search was carried out across these databases, covering the period from 2007 to 2024. The inclusion criteria encom pass studies on AMH and factors influencing ovarian reserve, that present either quantitative or qualitative data. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Analysis of the literature. The most important factor determining the level of AMH is age. In addition, factors that may influ ence hormone levels include genetic background, autoimmune diseases, polycystic ovary syndrome (PCOS), environmental toxins, diet, supplementation, oral contraception, physical activity, and smoking. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The causes of reduced OR and abnormal AMH levels remain unclear in many cases. Recommendations for the pre vention of pathologically reduced OR include lifestyle modifications, a diet rich in antioxidants, avoiding toxins, refraining from smoking, appropriate supplementation, genetic testing, and regular blood tests.